2020
DOI: 10.3390/cancers12082044
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Outcomes of Patients with Refractory or Relapsed FLT3-ITD Acute Myeloid Leukemia: A Toulouse-Bordeaux DATAML Registry Study

Abstract: Two recent phase 3 trials showed that outcomes for relapsed/refractory (R/R) FLT3-mutated acute myeloid leukemia (AML) patients may be improved by a single-agent tyrosine kinase inhibitor (TKI) (i.e., quizartinib or gilteritinib). In the current study, we retrospectively investigated the characteristics and real-world outcomes of R/R FLT3-internal tandem duplication (ITD) acute myeloid leukemia (AML) patients in the Toulouse-Bordeaux DATAML registry. In the study, we included 316 patients with FLT3-ITD AML tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
3
10
0
Order By: Relevance
“…Generally, patients with mutant FLT3 frequently accompanied with hyperleukocytosis [15] . Nevertheless, the effect of each mutation form, particularly Y842D, on clinical phenotype remains to be clari ed.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, patients with mutant FLT3 frequently accompanied with hyperleukocytosis [15] . Nevertheless, the effect of each mutation form, particularly Y842D, on clinical phenotype remains to be clari ed.…”
Section: Discussionmentioning
confidence: 99%
“…However, 4.4% of patients received a low-intensity regimen as a salvage treatment in DATAML study, whereas about 25% of patients received LDAC treatment in the QUANTUM-R study. This maybe a major factor contribute to the difference in response rate and OS between two studies [ 43 ]. A recent study demonstrated that glucocorticoids (GCs) enhance the antileukemic activity of FLT3 inhibitors in FLT3-mutant acute myeloid leukemia.…”
Section: Targeted Genes For R/r Amlmentioning
confidence: 99%
“…The Median OS of 7 months observed in the French study was also superior to the Quantum-R OS of 4.7 months. The authors argue that the possible bias, caused by the inclusion in the control arm of patients receiving low-intensity regimens, such as low-dose cytarabine or hypomethylating agents, might compromise the results of similar phase 3 trials [17].…”
Section: Gilteritinibmentioning
confidence: 99%